Analisis Kualitas Pelayanan Jasa dengan Metode SERVQUAL Fuzzy BRT Trans Jateng Koridor 1 Surakarta - Primasanti, Yunita; Oktaviana TD, Anita; Sebriana, Reva (Jurusan Teknik Industri, Institut Sains & Teknologi AKPRIND Yogyakarta, 2021)
BRT Trans Jateng corridor 1 Surakarta operates with the aim of helping reduce congestion and become one of the alternative modes of transportation chosen by the public from the city center to the suburbs or to the tourist destinations of sangiran museum. In its implementation, BRT Trans Jateng must comply with the minimum service procedure standards set by the Central Java Provincial Transportation Office. The purpose of this study is to analyze the level of service satisfaction in BRT Trans Corridor 1 Surakarta with fuzzy service quality method. The results of the analysis will be feedback for the Central Java Provincial Transportation Office to improve services to consumers. Based on the measurement of five dimensions of service quality, all dimensions have a negative value. Thus what is expected by customers who use BRT Trans Jateng services has not been in accordance with the reality received in the service. The results showed that the highest gap value of these five service quality dimensions, is Responsiveness with a value of 0.098 and the lowest gap value is the Assurance dimension with a value of 0.124. Keywords: service quality, Fuzzy Servqual, BRT Trans Jateng